Efficacy and Safety of Ergoferon in Children from 6 Months to 6 Years Old with Acute Respiratory Viral Infections in Contemporary Outpatient Practice: A Multicenter, Double-Blind, Placebo-Controlled Randomized Trial - N. A. Geppe; B. M. Blokhin; O. V. Shamsheva; S. T. Abdrakhmanova; K. A. Alikhanova; G. T. Myrzabekova (Canadian Respiratory Journal)
To evaluate the efficacy and safety of Ergoferon in combination with symptomatic therapy in children from 6 months to 6 years old with acute respiratory infections (ARI) in contemporary outpatient practice, an international, multicenter, double-blind, placebo-controlled, randomized, parallel-group clinical trial was performed. Derived by technological treatment of antibodies to interferon gamma, histamine, and CD4, Ergoferon was previously proved to modulate its molecular targets promoting effective antiviral protection. The data of 282 patients with oral temperature ≥38.0°C plus mild to moderate severity of flu-like nonspecific and nasal/throat/chest symptoms were included in intention-to-treat analysis (n = 140, Ergoferon group; n = 142, placebo group). Time to alleviation of all ARI symptoms was the primary endpoint, and 8 outcome measures were estimated as the secondary endpoints. Respiratory viruses were confirmed in 57.1% (Ergoferon) and 54.9% (Placebo) of patients. Compared to placebo, Ergoferon reduced time to alleviation of all ARI symptoms (4.5 ± 1.7 versus 5.2 ± 2.2 days in placebo; p=0.026) including fever (2.8 ± 1.5 vs 3.4 ± 2.0; p=0.031), flu-like nonspecific (4.0 ± 1.8 vs 4.7 ± 2.2, p=0.022), and nasal/throat/chest (4.3 ± 2.0 versus 5.0 ± 2.3; p=0.024) symptoms. Ergoferon add-on therapy decreased the mean total symptom severity score (according to 4-point scale for each symptom), ARI severity, frequency of antipyretic use, and percentage of complication requiring antibiotics and increased the percentage of recovered patients. The incidence of adverse events (AEs) in the Ergoferon group was significantly lower compared to the placebo group (7.0% versus 18.8%; p=0.004) including infectious diseases (3.5% vs 12.5%; p=0.008). In the Ergoferon group, AEs were mild or moderate. In 8 (57.1%) cases, AEs were unrelated to Ergoferon, in 5 (35.7%), the relationship was uncertain, and in 1 (7.1%), it was possible (mild rash on the face). Ergoferon treatment is beneficial for infants and young children with ARI in contemporary outpatient practice. Being well-tolerated, Ergoferon increases the symptomatic therapy effectiveness and improves the patient condition and disease outcomes.